2015
DOI: 10.3109/00498254.2015.1042946
|View full text |Cite
|
Sign up to set email alerts
|

Disposition, metabolism and mass balance of delafloxacin in healthy human volunteers following intravenous administration

Abstract: 1. The pharmacokinetics and disposition of delafloxacin was investigated following a single intravenous (300 mg, 100 µCi) dose to healthy male subjects. 2. Mean Cmax, AUC0-∞, Tmax and t1/2 values for delafloxacin were 8.98 µg/mL, 21.31 µg h/mL, 1 h and 2.35 h, respectively, after intravenous dosing. 3. Radioactivity was predominantly excreted via the kidney with 66% of the radioactive dose recovered in the urine. Approximately 29% of the radioactivity was recovered in the faeces, giving an overall mean recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
3
24
1
Order By: Relevance
“…We completed a multiple oral dose study of delafloxacin on the pharmacokinetics of a single oral dose of midazolam, a sensitive substrate for CYP3A . No interaction was found that is consistent with the aforementioned mass balance study and in vitro studies conducted with human liver microsomes (CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4/5) (data on file). In contrast, other antibiotics, such as ciprofloxacin, erythromycin, and clarithromycin, are potent inhibitors of CYP3A4 that result in drug‐drug interactions with drugs metabolized by this isoenzyme (eg, hydrocodone)…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We completed a multiple oral dose study of delafloxacin on the pharmacokinetics of a single oral dose of midazolam, a sensitive substrate for CYP3A . No interaction was found that is consistent with the aforementioned mass balance study and in vitro studies conducted with human liver microsomes (CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4/5) (data on file). In contrast, other antibiotics, such as ciprofloxacin, erythromycin, and clarithromycin, are potent inhibitors of CYP3A4 that result in drug‐drug interactions with drugs metabolized by this isoenzyme (eg, hydrocodone)…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study are consistent with our understanding of the disposition of delafloxacin in man. Following an intravenous dose of [ 14 C]delafloxacin in healthy subjects in a mass balance study, delafloxacin and its glucuronide metabolites were primarily excreted by the renal route, and only 29% excreted unchanged in the feces . A fraction of a delafloxacin dose is conjugated by the liver into glucuronidated metabolites for excretion by the kidneys, and this process is facilitated through the liver .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delafloxacin excretion is approximately two thirds in urine and one third in feces, primarily as unchanged drug. 86 The studies also found that delafloxacin was well tolerated, with the most common adverse effects being gastrointestinal and occurring more frequently at doses of 800 mg or above. Notably, no QTc interval prolongation occurred, which differentiates delafloxacin from other fluoroquinolones.…”
Section: Evidence Summary and Clinical Applicationmentioning
confidence: 93%
“…Additionally, the study confirmed that the main pharmacokinetic parameters were similar to those found in the aforementioned studies. Drug half-life was 2.35 h [17]. The pharmacokinetic parameters of delafloxacin (parent compound) and of other fluoroquinolones used in SSTIs are reported in Table 2.…”
Section: Pharmacokineticsmentioning
confidence: 99%